Elderly School in DKI Jakarta: Promoting Robust Elderly Health by Adopting the Lifelong Learning Concept - Tri Suratmi; Sarah Handayani; Dinni Agustin (Journal of Scientific Insights, 2026)
An aging population has occurred in DKI Jakarta Province, as data show the elderly population has exceeded 10% of the total population since 2020. Human aging occurs naturally, leading to declines in organ function and functional capacity. Innovative health promotion efforts are needed to effectively maintain the independence of the elderly and keep them healthy. The "Elderly School" (Sekolah Lansia/SL) is the intended innovation, initiated by Indonesia Ramah Lansia (IRL) and implemented as policy by the BKKBN, the leading sector in population. This study aims to evaluate the robustness of the elderly health promotion program implemented through the SMART Elderly School in DKI Jakarta since 2022. A mixed-method approach (quantitative and qualitative) was used to assess the implementation of the SMART Elderly School program, describe the characteristics of the elderly school participants in DKI Jakarta, and measure the quality of life of the elderly. The research population consisted of 129 elderly individuals who met the inclusion criteria. Data collection utilized questionnaires and the WHOQOL instrument to measure the quality of life of the elderly. Qualitative data were obtained through document studies, in-depth interviews, and participant observation. Qualitative data validation applied source and method triangulation techniques. Univariate quantitative data analysis was used to describe the characteristics and quality of life of the elderly. Qualitative data analysis used content analysis of in-depth interview transcripts and field notes. The results showed that the quality of life of the elderly school participants was in the high and very high categories, with characteristics varying across education, age, sex, marital status, and medical history over the past 2 (two) years. The implementation of the SMART Elderly School program in DKI Jakarta, as a robust elderly health promotion effort that adopts the concept of lifelong learning, is proven effective in maintaining the quality of life of the elderly.